Rouben Mamoulian papers - Mamoulian, Rouben
Correspondence, diaries, speeches, writings, scripts, production material, family papers, scrapbooks, printed matter, memorabilia and other papers relating to Mamoulian's career as a theatrical and film director and to his personal life. Includes files for film and theater productions spanning Mamoulian's entire career. Documents his Armenian heritage and contacts with other Armenians; interactions with individuals involved in the arts and entertainment of the twentieth century; innovations in sound, camera technique, and the use of color in film; participation in film festivals and retrospectives of his work; and association with the Directors Guild of America, Eastman School of Dance and Dramatic Action, Eastman School of Music, and Theatre Guild. Also documents the career of his mother, Virginie Mamoulian, as actress and director of the Armenian theater in Tiflis (T'bilisi, Georgia); his parent's activities in the Armenian community in California; the career of his wife and portrait artist, Azadia Mamoulian; and Mamoulian's interests including cats and pressed flowers.
Individuals represented include Maxwell Anderson, Fred Astaire, Pearl Bailey, Richard Bennett, Cyd Charisse, Maurice Chevalier, Jan Clayton, Gary Cooper, Linda Darnell, Bette Davis, Marlene Dietrich, Alfred Drake, Todd Duncan, Irene Dunne, Nanette Fabray, Greta Garbo, George Gershwin, Georgette Harvey, June Havoc, Ben Hecht, William Holden, Miriam Hopkins, Paul Horgan, Elissa Landi, Alfred Lunt, Ida Lupino, Charles MacArthur, Jeannette MacDonald, Fredric March, Nazimova, Tyrone Power, John Raitt, Joan Roberts, Mickey Rooney, William Saroyan, Randolph Scott, Elizabeth Taylor, Gene Tierney, H.G. Wells, and Tennessee Williams.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Rare Book and Special Collections Division.
Library of Congress Prints and Photographs Division.
Theatrical and film director. Born 1897; died 1987.
Collection material in English, with Armenian and Russian.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anderson, Maxwell, -- 1888-1959.; Astaire, Fred; Bailey, Pearl; Bennett, Richard, -- 1873-1944.; Charisse, Cyd; Chevalier, Maurice, -- 1888-1972.; Clayton, Jan; Cooper, Gary, -- 1901-1961.; Darnell, Linda, -- 1921-1965.; Davis, Bette, -- 1908-1989.; Dietrich, Marlene; Drake, Alfred, -- 1914-1992.; Duncan, Todd; Dunne, Irene, -- 1898-1990.; Fabray, Nanette; Garbo, Greta, -- 1905-1990.; Gershwin, George, -- 1898-1937.; Harvey, Georgette; Havoc, June; Hecht, Ben, -- 1894-1964.; Holden, William, -- 1918-1981.; Hopkins, Miriam, -- 1902-1972.; Horgan, Paul, -- 1903-1995.; Landi, Elissa, -- 1904-1948.; Lunt, Alfred; Lupino, Ida, -- 1918-1995.; MacArthur, Charles, -- 1895-1956.; MacDonald, Jeanette, -- 1903-1965.; Mamoulian, Azadia; Mamoulian, Virginie; March, Fredric, -- 1897-1975.; Nazimova, -- 1879-1945.; Power, Tyrone, -- 1869-1931.; Raitt, John, -- 1917-2005.; Roberts, Joan, -- 1917-2012.; Rooney, Mickey; Saroyan, William, -- 1908-1981.; Scott, Randolph, -- 1898-1987.; Taylor, Elizabeth, -- 1932-2011.; Tierney, Gene; Wells, H. G. -- 1866-1946.; Williams, Tennessee, -- 1911-1983.; Directors Guild of America; Eastman School of Dance and Dramatic Action; Eastman School of Music; Theatre Guild; Armenian Americans; Armenians -- Social life and customs; Armenians -- California; Armenians -- United States; Arts; Cats; Colors in motion pictures; Film festivals; Flowers -- Collection and preservation; Performing arts; Motion picture cameras; Motion picture industry; Motion pictures; Motion pictures -- Production and direction